2019
DOI: 10.1016/j.aca.2019.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Modeling solid-phase microextraction of volatile organic compounds by porous coatings using finite element analysis

Abstract: Experimental optimization of analytical methods based on solid-phase microextraction (SPME) is a complex and labor-intensive process associated with uncertainties. Using theoretical basics of SPME and finite element analysis software for the optimization proved to be an efficient alternative. In this study, an improved finite element analysis-based model for SPME of volatile organic compounds (VOCs) by porous coatings was developed mainly focussing on the mass transport in coatings. Benzene and the Carboxen/ p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…5 Furthermore, findings have shown that in some cases, mass transfer is not improved by increasing agitation at the sample phase; this is especially true for gaseous samples where analytes are extracted using high-adsorption-capacity materials (e.g., CAR/PDMS). 11 In another study, Xu et al described a mathematical model for SPME kinetics in semisolid samples matrices, which yielded a number of key findings. Specifically, in semisolid samples, mass transfer resistance increases during extraction, preloaded analytes' extraction and desorption are isotropic, and analytes with higher distribution constants deviate more significantly from the first-order kinetics.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…5 Furthermore, findings have shown that in some cases, mass transfer is not improved by increasing agitation at the sample phase; this is especially true for gaseous samples where analytes are extracted using high-adsorption-capacity materials (e.g., CAR/PDMS). 11 In another study, Xu et al described a mathematical model for SPME kinetics in semisolid samples matrices, which yielded a number of key findings. Specifically, in semisolid samples, mass transfer resistance increases during extraction, preloaded analytes' extraction and desorption are isotropic, and analytes with higher distribution constants deviate more significantly from the first-order kinetics.…”
mentioning
confidence: 99%
“…14 Other authors attempted to describe mass transport resistance in the heterogeneous coating but only considered tortuosity and porosity as parameters that contribute to effective diffusivity, which does not take into account analyte affinity for the sorbent, thus providing potentially skewing results as well. 11 The fundamental ideas of mass transfer into a liquid PDMS binder are well understood. In this paper, we utilize the finite element analysis software COMSOL Multiphysics (v.5.6) to develop numerical models that will provide a better understanding of how sorbents in a PDMS binder impact extraction kinetics, thereby resolving any misunderstandings regarding the mass transfer process.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Extraction and desorption times are important parameters of VOC quantification by SPME, which have an impact on intensity of analyte responses. Speed of equilibration during the extraction stage depends on a vessel volume, the diffusion coefficient of an analyte and its distribution constant between the coating and the air [35]. The equilibrium between the fiber and air for almost all analytes was reached after 5-10 min of extraction ( Figure 1).…”
Section: Effects Of Extraction and Desorption Timesmentioning
confidence: 99%